ANALISIS SITUASI PANGAN DAN GIZI UNTUK PERUMUSAN KEBIJAKAN OPERASIONAL KETAHANAN PANGAN DAN GIZI KABUPATEN LAMPUNG BARAT - Tabrani Mahfi; Budi Setiawan; Yayuk Farida Baliwati (Jurnal Gizi dan Pangan, 2008)
The objectives of this research were: 1) to know the situation of food and nutrition security in West Lampung District, 2) to know the strategic circumstance of food security, and 3) to formulate operational policy recommendation for food and nutrition security in West Lampung District. The primary data was obtained by interview and questionnaire filling in order to formulate alternatives of food security operational policy in West Lampung District. The secondary data was used to know the actual condition of food and nutrition security by using descriptive analysis and to formulate strategic circumstance of food security by using SWOT analysis. The result of the study showed that the situation of food security based on availability, shown by energy availability was 140% of Recommended Dietary Allowance (RDA) for energy (2 200 kcal/capita/day), while the protein availability was 74.28 gram/capita/day. The consumption in West Lampung  District reached 95.6% of RDA for energy in quantity, but only reaches Desirable Dietary Pattern Score 78.8 in quality. The strategic circumstance of food security in West Lampung  District was categorized in quadrant II (supporting diversification strategy). Thus, the first priority of policy recommendation is development of human resource.